Future-proof electricity prices for consumers - Bergaentzlé, Claire; Keles, Dogan (Samfundsøkonomen, 2023)
European electricity systems are undergoing unprecedented changes in response to the profound transformation of our modes of production from fossil fuels to decarbonised energy, to our shift to electricity for heating and transport, the emergence of decentralised energy sources (e.g. solar PV on the rooftop), and to the gas crisis we face. In response, the price formation and signals sent by both the electricity markets and the networks are changing, too. This article summarizes how the energy transition and the latest developments in the energy market affect prices and what policies and regulations can be introduced to keep energy consumption affordable.